A Comparative Study of the Clinical Benefits of Rivaroxaban and Warfarin in Patients With Non-valvular Atrial Fibrillation With High Bleeding Risk - Liu, Peng-Hui; Liu, Ze-Hua; Niu, Ming-Hui; Chen, Ping; Shi, Yuan-Bin; He, Fei; Guo, Rong (Frontiers in Cardiovascular Medicine, 2022)
Objective: To compare the clinical benefits of rivaroxaban and warfarin in patients with nonvalvular atrial fibrillation (NVAF) with high bleeding risk. Methods: A retrospective study was conducted on patients with high bleeding risk NVAF who were hospitalized at the First Affiliated Hospital of Zhengzhou University between May 31, 2016 and May 31, 2019 and who took at least rivaroxaban and warfarin. The clinical benefits of both drugs were assessed by efficacy benefit and safety risk. The primary efficacy benefit was a composite end point for stroke (both ischemic and hemorrhagic) and systemic embolism. The secondary efficacy end points were death and myocardial infarction(MI). The principal safety end point was the composite end point of fatal bleeding and critical organ bleeding. Results: A total of 1246 patients with high bleeding risk were enrolled, including 787 in the rivaroxaban group and 459 in the warfarin group. Results of the primary efficacy benefit endpoint were obtained from 104 patients (13.2%) in the rivaroxaban group and 88 (19.2%) in the warfarin group (hazard ratio [HR]: 0.681; 95% confidence interval [CI]: 0.512–0.906; P<0.001 for noninferiority). The principal safety end points were observed in 49 patients (6.23%) in the rivaroxaban group and in 55 patients (11.98%) in the warfarin group (HR: 0.469 in the rivaroxaban group; 95%CI: 0.314–0.702; P<0.001). Secondary efficacy and benefit endpoints: Overall, 28 (3.56%) patients in the rivaroxaban group and 22 (4.79%) in the warfarin group died, with an HR of 0.760 (95%CI: 0.435–1.329; P=0.336); 32 (4.07%) patients in the rivaroxaban group and 26 (5.66%) in the warfarin group had MI, with an HR of 1.940 (95% CI: 0.495–1.069, P=0.254) in the rivaroxaban group. Conclusions: Rivaroxaban is noninferior to warfarin in the prevention of stroke and systemic embolism in patients with high blood NVAF. Rivaroxaban is superior to warfarin in reducing fatal bleeding and bleeding in critical organs. Clinical Trial Registration: Chinese Clinical Trials Registry, identifier ChiCTR2100052454.